Performance Evaluation of Solar Oven Using Kapok Wool as Insulation Material - Abdulrahim, A. T.; Abdulkareem, S.; Haruna, M.; Abdulraheem, A. S.; Oluwole, F. A.; Ngala, G. M.; Mukhtar, U. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Solar ovens are among common devices which utilize insulation materials because of their ability to retards heat transfer by acting as barriers in the path of heat flow. Previous solar box cookers have used cotton, saw dust, and fibre-glass as insulation materials but none has used Kapok wool despite its potential. This study is aimed at the performance evaluation of solar oven using Kapok wool as the insulation material. The solar box oven designed is of the size 59 x 56 x 36cm dimensions made of plywood, with an aperture area of 3304cm2 double glass cover and an oven’s floor area of 1225cm2 made of aluminum. Kapok wool was used to line the oven’s walls and floor serving as insulator. The solar box oven was tested at the University of Maiduguri, Borno State, Nigeria. It was tested without load to determine its stagnation temperature and to check its endurance under stagnation conditions. Similarly, a water boiling test was conducted to cook rice and beans. The results show that  maximum stagnation temperature was 165.1°C and maximum overall daily thermal efficiency of 19.44% was achieved on a clear day test without reflector. The field test of the solar oven demonstrated its ability to cook rice and beans well with 1 kg of rice cooked under 2 hours, while 1 kg of beans was cooked under 1 hour 45 minutes on the same day. This performance demonstrated the suitability of Kapok wool as insulation material for solar ovens.